2013
DOI: 10.1016/j.pain.2013.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nociceptive effect of a conjugate of substance P and light chain of botulinum neurotoxin type A

Abstract: Neuropathic pain is a debilitating condition resulting from damage to sensory transmission pathways in the peripheral and central nervous system. A potential new way of treating chronic neuropathic pain is to target specific pain processing neurons based on their expression of particular receptor molecules. We hypothesized that a toxin-neuropeptide conjugate would alter pain by first being taken up by specific receptors for the neuropeptide expressed on the neuronal cells. Then, once inside the cell the toxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…The NK1r reduces the behavioral response to pain and the pain-induced c-Fos activation in distinct brain areas which are intimately linked with nociceptive neurotransmission and the initiation and integration of central stress responses [107]. Mustafa et al [108] have demonstrated that SP-BoNT/A LC conjugate can internalize BoNT/A LC selectively to NK1r-expressing neurons and delivers the LC inside the NK1r neurons. Internalized LC cleaves the SNAP-25 and can alleviate nociceptive behavior in a chemotherapy induced neuropathic pain [108].…”
Section: By Blocking the Release Of Neurotransmittersmentioning
confidence: 99%
“…The NK1r reduces the behavioral response to pain and the pain-induced c-Fos activation in distinct brain areas which are intimately linked with nociceptive neurotransmission and the initiation and integration of central stress responses [107]. Mustafa et al [108] have demonstrated that SP-BoNT/A LC conjugate can internalize BoNT/A LC selectively to NK1r-expressing neurons and delivers the LC inside the NK1r neurons. Internalized LC cleaves the SNAP-25 and can alleviate nociceptive behavior in a chemotherapy induced neuropathic pain [108].…”
Section: By Blocking the Release Of Neurotransmittersmentioning
confidence: 99%
“…A large body of evidence suggests that the N terminal of SP can be utilized to generate conjugated molecules without losing the ability of the peptide to bind and activate the NK1 receptor. This strategy has been successfully used for delivery of several different toxins including saporin (Mantyh et al, 1997), diphtheria (Benoliel et al, 1999), cholera (Caudle et al, 2007) and, more recently, botulinum toxin (Mustafa et al, 2013) ]tachykinins were linked together with the PWT2 core using a thio-Michael reaction. As in our results obtained using the N/OFQ sequence, the reaction proceeded in a few minutes and was characterized by an extremely high yield and purity of the final products: PWT2-SP, PWT2-NKA and PWT2-NKB.…”
Section: Bjp C Ruzza Et Almentioning
confidence: 99%
“…304 Coupling of the light chain of BoNT-A with substance P showed a beneficial role in treating chronic pain after intrathecal delivery. 305 …”
Section: Survey Of Current Targets Of Pain Therapeuticsmentioning
confidence: 99%